P08.04 Phototherapy with cancer-specific nanoporphyrin potentiates immunotherapy in bladder cancer. (21st September 2022) - Pan, C; Zhu, Z; Ma, A; Zhang, H; Lin, T; Farrukh, H; Li, Y; Lam, K
Abstract : Background: Immune checkpoint inhibitors (ICIs) in general have shown poor efficacy in bladder cancer (BCa). The purpose of this project is to determine whether photodynamic therapy (PDT) with BCa-specific porphyrin-based PLZ4-nanoparticles (PNP) potentiated ICI. Materials and Methods: SV40 T/Ras double-transgenic mice bearing orthotopic BCa and C57BL/6 mice carrying syngeneic bladder cancer models were used to determine the efficacy and conduct molecular correlative studies. Results: PDT with PNP generated reactive oxygen species, induced protein carbonylation, and dendritic cell maturation. In SV40 T/Ras double-transgenic mice carrying orthotopic bladder cancer, the median survival was 33.7 days in the control, compared to 44.8 (p=0.0123), 52.6 (p=0.0054) and over 75 (p=0.0001) days in the anti-PD-1, PNP PDT and combination groups, respectively. At Day 75 when all mice in other groups died, only one in 7 mice in the combination group died. For the direct anti-tumor activity, compared to the control, the ani-PD-1, PNP PDT and combination groups induced a 40.25% (p=0.0003), 80.72% (p<0.0001) and 93.03% (p<0.0001) reduction, respectively. For the abscopal anti-cancer immunity, the anti-PD-1, PNP PDT and combination groups induced tumor reduction of 45.73% (p=0.0001), 54.92% (p<0.0001) and 75.96% (p<0.0001), respectively. The combination group also diminished spontaneous and induced lung metastasis. Potential of immunotherapy by PNP PDT is multifactorial. Conclusions: In addition to its potential for photodynamic diagnosis and therapy, PNP PDT can synergize immunotherapy in treating locally advanced and metastatic bladder cancer. Clinical trials are warranted to determine the efficacy and toxicity of this combination. Disclosure Information: C. Pan: E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; LP Therapeutics. Z. Zhu: None. A. Ma: None. H. Zhang: None. T. Lin: None. H. Farrukh: None. Y. Li: None. K. Lam: E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; LP Therapeutics.